Pengaruh Partisipasi Anggaran Dan Kejelasan Sasaran Anggaran Terhadap Penyerapan Anggaran Dengan Komitmen Organisasi Sebagai Variabel Moderating Pada Badan Pengawas Pemilihan Umum Provinsi Sumatera Utara - Rudi Junjungan Sirait; Eka Nurmala Sari; Widia Astuty (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
The purpose of this study was to examine and analyze the effect of budget participation and clarity of budget targets on budget absorption moderated by direct or moderate organizational commitment. The approach used in this research is an explanatory approach. The population in this study is the entire Regency/Municipal General Elections Supervisory Agency of North Sumatra Province that conducts the 2020 regional elections, totaling 23 regencies/cities. The sample in this study was taken by 4 people from the General Election Oversight Board of the Regency / City of North Sumatra Province consisting of 23 korsek and 81 BAWASLU members so that the number of respondents was 104 people. Data collection techniques in this study used documentation studies, and questionnaires. The data analysis technique in this study uses a quantitative approach using statistical analysis by using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study prove that 1) Budget participation have a effect on budget absorption, 2) Clarity of budget targets have a significant effect on budget absorption, 3) Organizational commitment is not able to moderate the effect of budget participation on budget absorption, 4) Organizational commitment is not able to moderate the effect of clarity of budget targets on budget absorption of the General Elections Supervisory Agency of North Sumatra Province